Amyopathic Dermatomyositis, with anti-MDA5 antibody-associated RP- ILD - Wahinuddin Sulaiman (Asian Journal of Medicine & Health Sciences, 2021)
Clinically amyopathic form (CADM), a subset of dermatomyositis (DM) is characterized by classical cutaneous lesions that may progress without myopathy (Sontheimer criteria).[1] For more than three decades, anti-Jo-I autoantibody (histidyl transfer RNA (tRNA) synthetase) has been well established as one of the classic markers for polymyositis/dermatomyositis (PM/DM). [2] Myositis specific antibodies (MSAs) are new autoantibodies discovered in 70% of patients with idiopathic inflammatory myositis (IIM). [3] MSAs are found to be associated with distinct clinical phenotypes and prognosticate the underlying conditions. Anti-aminoacyl transfer RNA (tRNA) synthetases (ARS) have clinical significance in a small number of patients with idiopathic interstitial lung disease (ILD). [4] Other autoantibodies are equally important. However, the presence of anti-melanoma differentiationassociated gene 5 (MDA5) antibody had changed the clinical scenario in patients with DM for the last decades among other MSAs. Many case series or reports revealed that anti-MDA5 antibody was frequently detected in 50 -73% of patients with CADM and associated with rapidly progressive ILD (RP-ILD). [5,6,7,8] A study by Li et al had shown that the anti-MDA5 antibody is an important diagnostic biomarker for CADM as well as an unfavourable prognostic factor in the presence of RP-ILD